Systems analysis and design : international student version - Roth, Roberta M.; Dennis, Alan ;Wixom, Barbara Haley (Hoboken, New Jersey : Wiley, 2013)
"The 5th Edition of Dennis, Wixom, and Roth's Systems Analysis and Design continues to offer a hands-on, project based approach to SA & D that focuses on the core set of skills that all analysts must possess. Simply reading about systems analysis and design is not enough; students need to do it! Building on their experience as professional systems analysts and award-winning teachers, the authors capture the experience of developing and analyzing systems in a way no others can."--Provided by publisher.
pt. 1. Planning Phase -- Ch. 1. The System Analysts and Information Systems Development -- Ch. 2. Project Selection and Management -- pt. 2. Analysis Phase -- Ch. 3. Requirements Determination -- Ch. 4. Use Case Analysis -- Ch. 5. Process Modeling -- Ch. 6. Data Modeling -- pt. 3. Design Phase -- Ch. 7. The Design Phase, Design Strategy, and Architecture Design -- Ch. 8. User Interface Design -- Ch. 9. Program Design -- Ch. 10. Data Storage Design -- pt. 4. Implementation Phase -- Ch. 11. Moving into Implementation -- Ch. 12. Transition to the New System -- Ch. 13. The Movement to Objects.
Includes index.
Keywords: SYSTEM DESIGN